Paired kidney donation: are we going beyond reasonable limits in living-donor transplantation? - Medina-Pestana,José (2022)
Abstract The growing demand for transplant kidneys requires strategies to increase organ supply and avoid long waiting periods on the list. The increase in the number of transplants from living donors involves the growth in the use of unrelated donors and paired kidney donation. Most of these transplants are performed in the USA, where they already represent, respectively, 34% and 16% of total transplants from living donors. In Latin America, and especially in Brazil, there is no collective enthusiasm for these modalities, either at the request of transplanters or that of the community, with the region's priority being to increase transplants from deceased donors, which growth can be up to three-fold. Concerning transplants from matched donors, the possible conflicting results between donors can generate public challenges and they risk compromise the concepts of equal opportunities for transplant candidates, with the possibility of generating resistance to organ donation, especially in regions with socioeconomic limitations and disparities in access to qualified health care and education. This donation model involves challenging ethical and logistical issues, which are subject to questionings, starting with an act of exchange between two pairs until reaching embarrassing proposals, which can compromise the altruistic character of organ donation, and thus not be universally incorporated.